Improving Governance of the Pesantren through Human Resource Management - Rohmat, Rohmat; Sutiyono, Agus; Perdana, Muhammad Nabhan (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to find an effective format for boarding schools by implementing human resource management. This research uses qualitative research methods with a phenomenological approach. Data collection techniques use in-depth interviews, observations, and documentation. Meanwhile, data analysis techniques are carried out with Miles and Huberman's interactive analysis through data collection, data reduction, data presentation, and concluding. The results showed that: the management of educator resources is carried out through regeneration programs, coaching, and approaches to pesantren values. Preparation of educator resources through career development and training, and analysis. This research provides implications about the importance of governance of educational institutions through the implementation of human resources for the growth and development of institutions.